Realization of Fractional-Order Controllers: Analysis, Synthesis and Application to the Velocity Control of a Servo System - Barbosa, Ramiro S. (2011)
The synthesis and application of fractional-order controllers is now an active research field. This article investigates the use of fractional-order PID controllers in the velocity control of an experimental modular servo system. The system consists of a digital servomechanism and open-architecture software environment for real-time control experiments using MATLAB/Simulink. Different tuning methods will be employed, such as heuristics based on the well-known Ziegler-Nichols rules, techinques based on Bode's ideal transfer function and optimization tuning methods. Experiemntal responses obtained from the application of the several fractional-order controllers are presented and analyzed. The effectiveness and superior performance of the proposed algorithms are also compared with classical integer-order PID controllers.